Detection and Molecular Characteristics of Toxoplasma gondii DNA in Retail Raw Meat Products in Poland - Sroka, Jacek (Foodborne Pathog Dis, 2019)
Raw and undercooked meat are regarded as important sources of Toxoplasma gondii infection of people in Europe; however, data concerning this issue in Poland are still insufficient. The aim of this study was to determine the prevalence of T. gondii DNA isolated from raw meat products retailed in Poland. The molecular characteristics of detected DNA were also performed. Samples of cured bacon, raw or smoked sausages, ham, and minced meat were examined for the presence of T. gondii DNA. Samples were digested by pepsin solution, followed by the DNA isolation. Nested and real-time polymerase chain reaction (PCR) was performed based on the amplification of 35-fold-repetitive B1 fragment gene of T. gondii. For selected B1-positive samples, multiplex PCR was performed using SAG1, SAG2 (5′-SAG2 and 3′-SAG2), altSAG2, SAG3, GRA6, BTUB, C29-2, and L358 genetic markers. Amplicons were sequenced and analyzed with NCBI database. Among 3223 examined samples, 175 (5.4%) were PCR positive. The highest percentages of positive results were found for samples originating from south-east regions of Poland—Podkarpackie (17.9%), Małopolskie (12.6%), and Lubelskie (10.8%) (p < 0.001). The percentages of positive results for particular types of meat products—sausages, smoked meat products, ham, and minced meat—ranged from 4.5% to 5.8% and the differences between them were not significant (p > 0.05). Sequence analysis of selected B1-positive samples demonstrated mostly the alleles of clonal type III (49.0%), and less—type II (17.3%), and type I (10.2%) based on nine used genetic markers. The combinations of types I/II or II/III or I/III alleles at different loci were also found in 23.5% of cases. Detection of T. gondii DNA in raw meat products may indicate the potential health threat for consumers in Poland; however, for complete risk assessment of T. gondii infection, the additional studies, including detection of live parasite, are needed.